2019
DOI: 10.1177/0969141319876961
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding lung cancer screening behaviour using path analysis

Abstract: Objective Understanding lung cancer screening behaviour is crucial to identifying potentially modifiable factors for future intervention. Qualititative work has explored attitudes and beliefs about lung cancer screening from the perspective of the participant, but the theoretically grounded factors that influence screening-eligible individuals to screen are unknown. We tested an explanatory framework for lung cancer screening participation from the individual’s perspective. Methods Data were collected as part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
(36 reference statements)
3
32
0
Order By: Relevance
“…The lung cancer screening study (Carter-Harris et al, 2019; Draucker et al, 2019) conducted by our research team (referred to as the parent study) is first briefly summarized to provide the context for the discussion that follows describing the strategy we developed to select the interview sample. All strands of the parent study received approval from the Institutional Review Board (IRB) of the investigators’ institution.…”
Section: Connecting In a Study Of Lung Cancer Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The lung cancer screening study (Carter-Harris et al, 2019; Draucker et al, 2019) conducted by our research team (referred to as the parent study) is first briefly summarized to provide the context for the discussion that follows describing the strategy we developed to select the interview sample. All strands of the parent study received approval from the Institutional Review Board (IRB) of the investigators’ institution.…”
Section: Connecting In a Study Of Lung Cancer Screeningmentioning
confidence: 99%
“…A sample of 515 persons in the United States who currently or formerly smoked long-term and who were eligible for lung cancer screening per the United States Preventive Services Task Force (USPSTF) guidelines (American Cancer Society, 2016) (hereafter referred to as survey participants) were recruited by nationwide Facebook targeted advertisements. The conceptual model and the findings of the path analysis have been published (Carter-Harris et al, 2019). In summary, the path analysis revealed that a healthcare provider recommendation to screen, higher self-efficacy, and lower medical mistrust were directly associated with screening participation ( p < .05).…”
Section: Connecting In a Study Of Lung Cancer Screeningmentioning
confidence: 99%
“…Participants provided informed consent; all procedures were approved by the Institutional Review Board at Indiana University prior to participant recruitment. This study reports secondary analyses from a larger study on lung cancer screening; additional details on the sample and recruitment have been reported previously (Carter-Harris et al, 2019).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The engagement of users as information sources in social media greatly promotes the communication of health information. However, when compared with patient-provider professional health communication [36,49], interpersonal communication via the Internet and social media made a signi cant difference in women's effective screening behavior. Those who attempt to search for screening information through social media or are exposed to the communication of such screening information may be unable to choose advice appropriate and therefore have experienced ineffective CCS.…”
Section: Determinants and Mechanisms Of Ccsmentioning
confidence: 99%